Effects of harmful algal blooms on regulated disinfection byproducts: Findings from five utility case studies. Issue 3 (10th May 2021) - Foreman, Katherine; Vacs Renwick, Deborah; McCabe, Morgan; Cadwallader, Adam; Holsinger, Hannah; Kormondy, Charlene; Albert, Ryan
Abstract: During a cyanobacterial harmful algal bloom (HAB) event, drinking water treatment systems face the challenge of balancing acute and chronic health risks by treating the potentially toxin‐producing HAB and simultaneously managing for disinfection byproduct (DBP) formation. To explore the relationship between HAB events and DBP formation, a unique full‐scale study, including paired source water and finished water monitoring, was conducted at five drinking water utilities with HAB‐impacted source waters. Results confirm bench‐scale findings that HAB events in source water contribute to increases in DBP precursors. However, unlike results from laboratory studies, source water HAB‐related parameters and finished water DBPs were not consistently correlated at the five study utilities. These different outcomes suggest regulated DBP formation in utilities with HAB‐impacted source water is complex and influenced by a variety of site‐specific conditions, including source water conditions and data available for operational decision‐making, timing of treatment adjustments, and key operational choices.